2022
DOI: 10.3389/feart.2021.763050
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Distribution and Evolution of WNW-Directed Faults in the Liaodong Bay Subbasin of the Bohai Bay Basin, Eastern China

Abstract: WNW-directed faults are widespread in eastern China, but debates regarding their distributions and evolutionary processes remain unsettled. Based on the latest 3-D seismic data, a series of WNW-directed faults south of the Liaodong Bay subbasin was identified, for which the evolution and formation mechanisms were discussed. The results show that four WNW-directed faults are characterized by poor continuity and nearly parallel orientations. Vertically, they exhibit listric geometries and cut through Paleozoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 124 publications
0
1
0
Order By: Relevance
“…Initially, it was believed that the fault characteristics in Cenozoic basins in eastern China were caused solely by simple extensional stress. However, subsequent studies revealed that pre-existing structures (such as faults, basement structures, and salt structures) within rift basins significantly impact fault characteristics [33,34]. Additionally, multi-phase extension leads to localized stress rotation and complex fault characteristics [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was believed that the fault characteristics in Cenozoic basins in eastern China were caused solely by simple extensional stress. However, subsequent studies revealed that pre-existing structures (such as faults, basement structures, and salt structures) within rift basins significantly impact fault characteristics [33,34]. Additionally, multi-phase extension leads to localized stress rotation and complex fault characteristics [14,20].…”
Section: Introductionmentioning
confidence: 99%